2020
DOI: 10.1007/s13205-020-02302-5
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas mediated base editing: a practical approach for genome editing in oil palm

Abstract: The improvement of the yield and quality of oil palm via precise genome editing has been indispensable goal for oil palm breeders. Genome editing via the CRISPR/Cas9 (CRISPR-associated protein 9) system, ZFN (zinc finger nucleases) and TALEN (transcription activator-like effector nucleases) has flourished as an efficient technology for precise target modifications in the genomes of various crops. Among the genome editing technologies, base editing approach has emerged as novel technology that could generate si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
(51 reference statements)
0
14
0
2
Order By: Relevance
“…The updated physical genome coverage of 79% from the earlier 43%, has successfully placed 1968 unassigned scaffolds onto the genome which extended the 16 pseudochromosomes thus, enhancing its overall quality (Ong et al, 2020). Leveraging the available oil palm genome databases as well as next generation sequencing technologies, Zhou et al (2020) and identified candidate genes, potential pathways as well as transcription factors likely to be involved in drought tolerance in the oil palm. Aside from drought, EgMYB transcription factors (Zhou et al, 2020) were also found to be differentially expressed when exposed to other stresses such as cold and salinity.…”
Section: Mitigating the Changing Environment Through Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The updated physical genome coverage of 79% from the earlier 43%, has successfully placed 1968 unassigned scaffolds onto the genome which extended the 16 pseudochromosomes thus, enhancing its overall quality (Ong et al, 2020). Leveraging the available oil palm genome databases as well as next generation sequencing technologies, Zhou et al (2020) and identified candidate genes, potential pathways as well as transcription factors likely to be involved in drought tolerance in the oil palm. Aside from drought, EgMYB transcription factors (Zhou et al, 2020) were also found to be differentially expressed when exposed to other stresses such as cold and salinity.…”
Section: Mitigating the Changing Environment Through Technologymentioning
confidence: 99%
“…Leveraging the available oil palm genome databases as well as next generation sequencing technologies, Zhou et al (2020) and identified candidate genes, potential pathways as well as transcription factors likely to be involved in drought tolerance in the oil palm. Aside from drought, EgMYB transcription factors (Zhou et al, 2020) were also found to be differentially expressed when exposed to other stresses such as cold and salinity.…”
Section: Mitigating the Changing Environment Through Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The available gene pool has now been greatly (123). Recent breeding-related reviews include genomics (124,125), genomic selection (126), transgenics (6), genome editing (127), and marker-assisted selection (128,129). Following the publication of the OP genome sequence in 2013 (130), several detailed linkage maps have now become available for the use of breeders (131,132).…”
Section: Breeding and Biotechnologymentioning
confidence: 99%
“…An alternative to transgenic crop manipulation is the used of so-called cisgenic approaches such as genome editing. Specific applications of genome editing to OP breeding via CRISPR have been reviewed recently by Yarra et al (127). Modern crop breeding is also able to profit from a host of advanced technologies such as association genetics (141), molecular mutagenesis including TILLING (TargetIng Local Lesions IN Genomes) and marker-assisted selection (142).…”
Section: Breeding and Biotechnologymentioning
confidence: 99%